Voluntary sport programs for individuals with mental health disorders: The trainer’s and participant’s view - Florence Epiney; Carina Baumberger; Carole Pauli; Daniela Loosli; Hansjörg Znoj; Birgit Kleim; Frank Wieber; Nikolai Kiselev (Current Issues in Sport Science, 2024)
Introduction